Management of orbital and brain complications of sinusitis: A practical algorithm. Issue 12 (December 2021) - Raponi, Ingrid; Giovannetti, Filippo; Buracchi, Matteo; Priore, Paolo; Battisti, Andrea; Scagnet, Mirko; Genitori, Lorenzo; Valentini, Valentino
Abstract: The aim of this work was to present a practical management algorithm for orbital and brain complications of sinusitis. According to the inclusion criteria, a sample of 68 patients was collected between 2008 and 2018 (39 males and 29 females). Among them, 44 were adults, with a mean age of 50.46 years, and 24 were pediatric patients, with a mean age of 10.33 years. Oral or intravenous antibiotic therapy was administered to all patients. Pharmacological resolution was observed in 14 cases. Early surgical treatment within 48 hours was necessary in 10 cases. Surgery consisted of abscess drainage, associated or not with functional endoscopic sinus surgery. Delayed surgery within 15–30 days was performed in 44 patients. The core procedure was functional endoscopic sinus surgery. Subsidiary procedures were abscess drainage, tooth extraction or cranial base repair. The combination of two or more of these procedures was case selected. Median follow-up was of 46.36 months. Sinusitis complications necessitate rapid diagnosis and prompt treatment. Antibiotic therapy alone is enough for mistreated rhinosinusitis with no anatomical predisposing factor. Surgery is mandatory for altered nasal and paranasal sinus anatomy or odontogenic infections.